2011
DOI: 10.1007/s11430-010-4047-3
|View full text |Cite
|
Sign up to set email alerts
|

Sources and distribution of polycyclic aromatic hydrocarbons of different glaciers over the Tibetan Plateau

Abstract: Twenty snow samples were collected from the Qiyi glacier in Qilian Mountains, the Yuzhufeng glacier in eastern Kunlun Mountains, the Xiaodongkemadi glacier in Tanggula Mountains, and the Gurenhekou glacier in Nyainqêntanglha Range over the Tibetan Plateau. The concentration and distribution features of sixteen priority Polycyclic Aromatic Hydrocarbons (PAHs) were determined by gas chromatography equipped with a mass spectrometry detector (GC-MS). The sources of these PAHs were explored as well. Our results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 47 publications
0
17
1
1
Order By: Relevance
“…In fact, more volatile low molecular weight compounds move farther and are more likely to enter remote regions, whereas high molecular weight ones have higher affinity to the surface of atmospheric particles on which they are preferentially adsorbed during their migration. Before reaching remote regions, they may be deposited and often stored in the soil-water-plant systems [22][23][24][25][26]. Similar to those in remote areas, PAHs found in glaciers over the Tibetan Plateau were dominantly low molecular weight compounds due to the long distance of the glaciers from the source regions [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, more volatile low molecular weight compounds move farther and are more likely to enter remote regions, whereas high molecular weight ones have higher affinity to the surface of atmospheric particles on which they are preferentially adsorbed during their migration. Before reaching remote regions, they may be deposited and often stored in the soil-water-plant systems [22][23][24][25][26]. Similar to those in remote areas, PAHs found in glaciers over the Tibetan Plateau were dominantly low molecular weight compounds due to the long distance of the glaciers from the source regions [22].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, concentration levels of each individual PCB or PAH may vary unpredictably, which in turn may cause discrepancy of the distribution pattern of low and high molecular weight compounds in environmental records, i.e. sediments, snow/firn/ice, between developed and remote/pristine areas [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent measurements of organic compounds at high altitude or high latitude sites point to the potential impact of topography and air mass transport on the organic content of snow. The deposition of organic compounds in the Himalayas has been found to be a seasonally dependent function of air mass transport from China and Central Asia, as evidenced in measurements of 16 polycyclic aromatic hydrocarbons (PAH) over glaciers of the Tibetan Plateau (Li et al, 2011) and detection of specific persistent organic pollutants (POP), e.g., organochlorine pesticides and polychlorinated biphenyls, in the snow of a Himalayan glacier (Kang et al, 2009). Usenko et al (2010) observed similar impacts of topography on the atmospheric transport and deposition of PAHs in high elevation sites of some Western US National Parks.…”
Section: Introductionmentioning
confidence: 99%
“…PAHs are produced by both biomass burning and fossil fuel burning (Macdonald et al, 2000 and references therein) (see also 3.4.3). The ratio of specific PAHs released during vegetation combustion may help identify samples containing forest fire signatures (Li et al, 2011;Masclet et al, 2000;Slater et al, 2002). In addition, burning vegetation produces carbon particles and gases containing "modern" levels of 14 C, while compounds from fossil fuel combustion do not contain the heavy carbon isotope (Slater et al, 2002).…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%